2013
DOI: 10.1155/2013/879563
|View full text |Cite
|
Sign up to set email alerts
|

Virtual/Real Transfer in a Large-Scale Environment: Impact of Active Navigation as a Function of the Viewpoint Displacement Effect and Recall Tasks

Abstract: The purpose of this study was to examine the effect of navigation mode (passive versus active) on the virtual/real transfer of spatial learning, according to viewpoint displacement (ground: 1 m 75 versus aerial: 4 m) and as a function of the recall tasks used. We hypothesize that active navigation during learning can enhance performances when route strategy is favored by egocentric match between learning (ground-level viewpoint) and recall (egocentric frame-based tasks). Sixty-four subjects (32 men and 32 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
19
1
3
Order By: Relevance
“…Our results do not support the notion that active learning is beneficial to spatial knowledge acquisition (e.g., Péruch et al, 1995;Wallet et al, 2013). Passive (rather than active) participants were able to manage an increase in cognitive load.…”
Section: Cognitive Loadcontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results do not support the notion that active learning is beneficial to spatial knowledge acquisition (e.g., Péruch et al, 1995;Wallet et al, 2013). Passive (rather than active) participants were able to manage an increase in cognitive load.…”
Section: Cognitive Loadcontrasting
confidence: 99%
“…We cannot be certain as to whether our results apply to spatial stimuli other than maps, as physical and motor feedback could play a role in spatial knowledge acquisition. Whether spatial knowledge is acquired from maps or through navigation has been shown to have an effect on the recall of the studied environment (Münzer et al, 2006;Thorndyke & Hayes-Roth, 1982;Wallet et al, 2013). Wallet et al observed that active navigation was primarily beneficial for ground-level navigation by comparison with an aerial perspective.…”
Section: Cognitive Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…The first term of the cognitive map used by Tolman to mean the cognitive map is the description of the mental representation of spatial information and it is the internal (mentally) representation of spatial environments [49]. The cognitive map used to solve the spatial problems (visualization) such that we need in our research by the navigation as many types of research conclude it [50], [51].…”
Section: ) Navigationmentioning
confidence: 99%